Genealogical Traces of al-Bayḍāwī’s Anwār al-Tanzīl in Qur’anic Manuscript from Bali - Wijaya, Krisna Hadi; Bakhri, Syamsul (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2025)
A notable aspect of the discovery of an ancient Qur’anic manuscript in the Bugis Suwung Village, Bali, is the presence of hadiths on faḍā’il al-suwar (the virtues of the Qur’anic surahs) inscribed on either side of each surah. Nevertheless, this specific domain has not been the subject of any prior study. The present paper, therefore, examines the genealogical and constructive relationship of this domain with the genealogical influences of al-Bayḍāwī in the Archipelago. Adopting a historical approach that incorporates Walid Saleh’s genealogical tradition, this study uses data from authoritative sources and associated documentary evidence. The findings indicate that these ḥadīths are directly sourced from al-Bayḍāwī’s Anwār al-Tanzīl as ‘inherited corpus materials’. Despite being categorized as mawḍu‘ (fabricated), these hadiths are recognized as a catalyst for Qur’anic learning, with the objective of encouraging a deepened love for the Qur’an within the context of a minority Muslim community situated within a predominantly Hindu Balinese cultural milieu. This 17th-century manuscript, adorned with Bugis-Makassar artistic styles, offers historical evidence of the transmission and adaptation of the classical exegetical tradition within the local cultural landscape. This study contributes to the discourse of Islamic intellectual history in the Archipelago by highlighting the dialectical dynamics among religious texts, pedagogical practices, and local socio-cultural contexts. It also demonstrated that, despite its status as a Qur’anic manuscript, the text is associated with the genealogical tradition of tafsīr.